Description of a Neotropical New Species of OxysarcodexiaTownsend, 1917 (Diptera: Sarcophagidae) - Souza, Carina Mara de; Paseto, Maria Lígia (EntomoBrasilis, 2015)
Abstract. A new species of Oxysarcodexia Townsend, 1917 (Diptera: Sarcophagidae) from Brazil is described based on male specimens. This is a mainly Neotropical genus of flesh flies, with few species also present in Nearctic, Australasian and Oceanian Regions. Its species have been associated with decomposing organic matter (feces of mammals or birds – dung-breeders species) and have potential forensic importance when associated with carcasses (attracted fauna and, in some cases, true carrion-breeding species). Digital photographs of the habitus in lateral view and of the terminalia in lateral, posterior and ventral views are provided. Oxysarcodexia mineirensis sp. n. is close-related to “Xarcophaga species-group” (i.e. with a postero-distal phallic enlargement) and is similar to Oxysarcodexia favorabilis (Lopes, 1935) due to the conformation of the terminalia, especially the phallus flower-like shaped. Descrição de Uma Nova Espécie Neotropical de Oxysarcodexia Townsend, 1917 (Diptera: Sarcophagidae) Resumo. Uma nova espécie de Oxysarcodexia Townsend, 1917 (Diptera: Sarcophagidae) é descrita com base em espécimes machos. As espécies deste gênero de sarcofagídeos apresentam distribuição majoritariamente Neotropical, com algumas espécies ocorrendo também nas regiões Neártica, Australásia e Oceânica. As espécies deste gênero podem ser encontradas associadas à matéria orgânica em decomposição (fezes de mamíferos ou aves – espécies coprófilas) e podem apresentar importância forense quando associadas a carcaças (fauna atraída e, em alguns casos, espécies que se criam). Fotografias digitais do hábito em vista lateral e da terminália em vistas lateral, posterior e ventral são apresentadas. Oxysarcodexia mineirensis sp. n. pertence ao “grupo Xarcophaga” (i.e. possui o falo alargado postero-distalmente) e contém similaridades com Oxysarcodexia favorabilis (Lopes, 1935) devido à conformação da terminália, especialmente o formato do falo, semelhante a uma flor.